Test‐retest properties of the Patient Reported Outcomes, Burdens and Experiences (PROBE) questionnaire and its constituent domains. Issue 1 (6th December 2018) - Chai‐Adisaksopha, Chatree; Skinner, Mark W.; Curtis, Randall; Frick, Neil; Nichol, Michael B.; Noone, Declan; O'Mahony, Brian; Page, David; Stonebraker, Jeffrey; Thabane, Lehana; Crowther, Mark A.; Iorio, Alfonso
Abstract : Background: The Patient Reported Outcomes, Burdens and Experiences (PROBE) study aims to develop and validate questionnaire for assessing health status in patients with haemophilia and participants without bleeding disorders. Objective: To investigate the test‐retest properties of the PROBE questionnaire. Methods: The PROBE questionnaire covers four domains and is comprised of 29 questions. People with haemophilia (PWH) and participants without bleeding disorder were invited to participate in this study. All participants were asked to complete the PROBE questionnaire three times (paper‐based survey on two consecutive days: T1 and T2 and then a web‐based version: T3). Test‐retest properties and percentage agreement were analysed. Results: A total of 63 participants were enrolled in this study with a median age of 50 (range: 17‐76) years. Of these, 30 (47.6%) were PWH. On the questions common to PWH and participants without bleeding disorder, Kappa coefficients ranged from 0.69 to 1.00, indicating substantial to almost perfect agreement (T1 vs T2). For haemophilia‐related questions (T1 vs T2), Kappa coefficients ranged from 0.5 to 1.0. Of these, 5 of 11 items were in perfect agreement (Kappa = 1.0). The web‐based questionnaire (T3) showed substantial to almost perfect agreement with the paper version (T1 test‐retest properties were comparable between PWH and individuals without a bleeding disorder). Conclusions: The results suggest that PROBE is a reliable tool to assess patient‐reported outcomes for PWH and benchmark data in participants without bleeding disorder. The web‐based questionnaire and the standard paper‐based version can be used interchangeably.